Dietary inclusion of chestnut (Castanea sativa) polyphenols to Nile tilapia reared in biofloc technology: Impacts on growth, immunity, and disease resistance against Streptococcus agalactiae - Hien Van Doan (2020)
© 2020 Elsevier Ltd A feeding trial was carried out to examine the effects of adding chestnut (Castanea sativa) polyphenols (CSP) on the growth, skin mucus and serum immune parameters of Nile tilapia (Oreochromis niloticus). Five experimental diets with inclusion levels of 0, 1, 2, 4, and 8 g kg−1 of CSP were fed to Nile tilapia fingerlings (12.77 ± 0.17 g fish−1) during an eight-week trial. Fish were analyzed on the fourth and eighth week to determine the influences of CSP on growth, skin mucus, and serum immune parameters. Challenging test versus Streptococcus agalactiae was evaluated at the end of the trial. Fish fed with CSP enriched diets displayed a significant increase (P ≤ 0.05) in growth and a decline in feed conversion ratio (P ≤ 0.05). Similarly, skin mucus and serum immune parameters were significantly increased (P ≤ 0.05) in fish fed CSP with respect to the control. The effects were already evident four weeks after the CSP administration. The disease protection test displayed that the fish's survival rate was significantly higher (P < 0.05) in CSP diets over the control. The relative percentage of survival (RSP) was 62.5, 75.0, 58.3, and 37.5 in fish fed diets contained 1, 2, 4, and 8 g kg−1 CSP, respectively. The best effect on growth, immune response, and disease resistance were shown in Nile tilapia fed with a diet supplementation of 2 g kg−1 CSP.